Has education become more positional? Educational expansion and labour market outcomes, 1985–2007. (May 2015) - Bol, Thijs
Educational expansion has had important effects on society. However, it has not yet been acknowledged that expansion might have changed the way in which education operates in labour markets. We argue that, as a result of educational expansion, a positional model of education becomes more important whereby labour market rewards do not primarily depend on absolute skill levels, but instead on workers' relative positions in the labour market. Analyzing data from the International Social Survey Programme from 1985 to 2007 for 28 countries, we find support for the claim that education has become increasingly positional with educational expansion.